Sentinel-1 interferometry with ionospheric correction from global and local TEC maps for land displacement detection in Taiwan. Issue 5 (1st March 2020) - Liao, Wan-Ting; Tseng, Kuo-Hsin; Lee, I-Te; Liibusk, Aive; Lee, Jui-Chi; Liu, Jann-Yenq; Chang, Chung-Pai; Lin, Yu-Ching
Abstract: Sentinel-1 satellite launched by the European Space Agency (ESA) offers an opportunity to apply the differential interferometric synthetic aperture radar (DInSAR) in 12-day revisit, a potential solution to effectively measure surface deformation. However, for areas affected by the Equatorial Ionization Anomaly (EIA) in a global ionosphere pattern, the total electron content (TEC) irregularity between snapshots may induce extra fringes and further mislead the unwrapping and displacement results. To test the necessity of ionospheric correction, we utilize global and regional ionospheric vertical TEC maps, namely the Global Ionosphere Map (GIM) released by the International GNSS Service and the Taiwan Regional Ionospheric Map (TRIM) provided by a local GNSS network, to compensate ionospheric phases in the interferograms. Our experiments investigate 47 ascending image pairs in 2016 and 2017. Among them, two pairs of images whose differenced TEC ( Δ TEC) stronger than 16.73 TEC unit in azimuthal gradient contain the clearest extra fringes. The results show that TRIM outperforms in reducing extra fringes caused by the ionospheric effect, with a root-mean-square error (RMSE) of the estimated satellite line-of-sight displacement reduced from 105.03 mm to 9.94 mm as compared against ground truth data. We conclude that TRIM TEC map is able to remove long-wavelength background of ionosphere-induced displacement when a differenced TEC gradient larger than an empirical threshold of 15 TECU.